Music Education and Sustainability in Lombok, Indonesia - David Harnish (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
This article discusses the challenges of teaching and sustaining music and other performing arts on the island of Lombok in Indonesia. It follows my field research trajectory on the island over a period of 34 years and analyzes the efforts of government interventions, non-government actors, and teachers and educational institutions in the transmission and sustainability of the arts. Interpretations indicate that a combination of globalization, urbanization, social media, everyday mediatization, and Islamization over recent decades negatively impacted traditional musics in specific ways, by problematizing sustainability. However, several agents–individuals inside and outside the government who understood the situation and had the foresight to take appropriate action–developed programs and organizations to maintain or aestheticize the performing arts, sustain musician livelihoods, and engage a new generation of male youth in music and dance. These efforts, supplemented by the formation of groups of leaders dedicated to the study of early culture on Lombok and fresh initiatives in music education, have ushered in new opportunities and visibility for traditional music and performing arts and performing artists.